2021
DOI: 10.1016/j.cegh.2021.100838
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use pattern and quitting behaviour among healthcare professionals during the COVID-19 pandemic: Insights from a pan India online survey

Abstract: Background Healthcare professionals (HCPs) have a definite role in tobacco control and can help immensely by setting examples. The current study aimed to study the tobacco use pattern and quitting behaviour among HCPs of India during the COVID-19 pandemic. Methods We addressed the research objective using a cross-sectional, anonymous online survey using ‘google form” among 687 HCPs of India during December 2020. Descriptive and inferential statistics were performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…The proportion of adolescents and young adults quitting or attempting to quit ranged from about 7% to 30%, 49 , 50 , 66 , 78 and the proportion of adults ranged from 1·1% to 50%. 46 , 47 , 48 , 53 , 79 , 80 , 81 , 82 Furthermore, some studies showed that men were less likely than women to stop using cigarettes or e-cigarettes during the pandemic; 54 , 58 , 80 however, other studies showed that men were more likely than women to quit tobacco use. 69 Some of the same studies showed that alcohol use increased and physical activity decreased during the pandemic, 50 , 61 , 76 , 82 , 83 , 84 although others have reported declines in alcohol use.…”
Section: Tobacco Product Use Behaviours During the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of adolescents and young adults quitting or attempting to quit ranged from about 7% to 30%, 49 , 50 , 66 , 78 and the proportion of adults ranged from 1·1% to 50%. 46 , 47 , 48 , 53 , 79 , 80 , 81 , 82 Furthermore, some studies showed that men were less likely than women to stop using cigarettes or e-cigarettes during the pandemic; 54 , 58 , 80 however, other studies showed that men were more likely than women to quit tobacco use. 69 Some of the same studies showed that alcohol use increased and physical activity decreased during the pandemic, 50 , 61 , 76 , 82 , 83 , 84 although others have reported declines in alcohol use.…”
Section: Tobacco Product Use Behaviours During the Pandemicmentioning
confidence: 99%
“… 45 , 47 , 52 , 77 , 86 , 87 Such perceived risk of infection or disease severity, or concern over lung health more generally, was associated with reduced tobacco use. 49 , 79 , 80 , 86 , 88 , 89 , 90 , 91 , 92 Additional reasons for reduced tobacco use included wanting to help others who might have COVID-19; 88 concerns that parents might learn about their use; 49 and closure of bars and pubs, suspension of classes, and reduced socialising with friends. 52 Those with chronic illness were also more likely to reduce tobacco use during the pandemic.…”
Section: Tobacco Product Use Behaviours During the Pandemicmentioning
confidence: 99%
“…A single study examined knowledge of smoking and smokeless tobacco form (i.e. chewing tobacco) to be harmful for COVID-19 and found a positive association in doctors and nurses in India [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to US Centers for Disease Control data, 25% of nurses worldwide consume tobacco products. Studies conducted during the COVID-19 pandemic indicated that a high percentage of nurses consumed tobacco, alcohol or other substances due to anxiety, stress and the effect of the pandemic [ 20 , 21 ]. In 2019, Nilan et al published a systematic review and meta-analysis of the prevalence of tobacco use in healthcare workers.…”
Section: Discussionmentioning
confidence: 99%